2022
DOI: 10.1371/journal.pone.0270162
|View full text |Cite
|
Sign up to set email alerts
|

Community succession and straw degradation characteristics using a microbial decomposer at low temperature

Abstract: This study explored changes in the microbial community structure during straw degradation by a microbial decomposer, M44. The microbial community succession at different degradation periods was analyzed using MiSeq high-throughput sequencing. The results showed that 14 days after inoculation, the filter paper enzyme and endoglucanase activities increased to 2.55 U·mL-1 and 2.34 U·mL-1. The xylanase, laccase, and lignin peroxidase activities rose to 9.86 U·mL-1, 132.16 U·L-1, and 85.43 U·L-1 after 28 d, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Depending on the design and the duration of the experiment on the straw decomposition, two or three phases could be distinguished in a process of microbial succession [21,22,31]. Our data allowed us to distinguish three phases of bacterial succession during the decomposition of lignocellulosic subtract: early (1st month), middle (2nd month), and late (3rd month).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Depending on the design and the duration of the experiment on the straw decomposition, two or three phases could be distinguished in a process of microbial succession [21,22,31]. Our data allowed us to distinguish three phases of bacterial succession during the decomposition of lignocellulosic subtract: early (1st month), middle (2nd month), and late (3rd month).…”
Section: Discussionmentioning
confidence: 93%
“…Multiple studies have shown that during the composting of untreated straw with a natural epiphytic microbiome, the microbial community undergoes taxonomic and functional succession [21,22]. The aim of this study was to isolate the cellulolytic community from the soil and study its full succession stages in sterile straw.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the design and the duration of the experiment on the straw decomposition, two or three phases could be distinguished in a process of microbial succession [ 21 , 22 , 35 ]. Our data allowed us to distinguish three phases of bacterial succession during the decomposition of lignocellulosic subtract: early (first month), middle (second to third month), and late (fourth to sixth month).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that during the composting of untreated straw with a natural epiphytic microbiome, the microbial community undergoes taxonomic and functional succession [ 21 , 22 ]. Meanwhile, straw introduction into the soil creates a surplus of nutrients, specifically carbon compounds, which facilitates a new path in the microbiota succession [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the results of this study. Temperature has a significant impact on straw decomposition, and the in situ decomposition rate of straw is often slow under low-temperature conditions [36]. It has been reported that the microbial straw decomposition additive can raise the environmental temperature, which improves the decomposition effect of straw [37,38].…”
Section: Effect Of Microbial Agents and Mulch Film Covering On The Ph...mentioning
confidence: 99%